Management of severe tetanus in Afghanistan: lessons from the field - Ornella Spagnolello; Ahmad K Aryan; Muhebullah Ahmadzai; Arezo Dost; Abdul G Boosti; Giancarlo Ceccarelli; Gina Portella; Martina Baiardo Redaelli (Journal of Infection in Developing Countries)
Introduction: Tetanus is a rather rare disease in the Western countries thanks to widespread vaccination programs and the availability of prophylactics for patients with tetanus-prone injuries. The few cases that do occur are promptly managed in intensive care units (ICUs). However, tetanus is not so rare in developing countries, where access to a suitable level of care is limited. An unstable political situation can be a significant factor influencing patient outcomes.